2015
DOI: 10.1614/wt-d-14-00078.1
|View full text |Cite
|
Sign up to set email alerts
|

Imazapic Activity in a Semiarid Climate in Downy Brome (Bromus tectorum)–Infested Rangeland and CRP Sites

Abstract: Chemical control of downy brome has focused on imazapic; however, imazapic efficacy in semiarid climates is unpredictable, possibly because of variable residual soil activity. Our objective was to characterize imazapic activity over 9 mo in rangeland and a Conservation Reserve Program (CRP) site following its application in the fall as affected by rate (0, 80, 160, 240 g ai ha−1) and quantity of plant residue (reduced, ambient). Greenhouse bioassays were conducted over two seasons (2010 to 2011 and 2011 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…These results, showing that herbicides had minimal effect on B. tectorum, highlight the inconsistency in the ability of herbicides to reduce B. tectorum abundance, especially with only limited herbicide application (two years for spring glyphosate but only one year for fall applications due to low fall germination in 2016). Previous studies have measured the effective control of B. tectorum via imazapic [28,29,43,44] and rimsulfuron [30,45], although a review of imazapic efficacy studies (n = 24) in Montana showed effective but variable results, with one year of application [29].…”
Section: Herbicidementioning
confidence: 99%
See 1 more Smart Citation
“…These results, showing that herbicides had minimal effect on B. tectorum, highlight the inconsistency in the ability of herbicides to reduce B. tectorum abundance, especially with only limited herbicide application (two years for spring glyphosate but only one year for fall applications due to low fall germination in 2016). Previous studies have measured the effective control of B. tectorum via imazapic [28,29,43,44] and rimsulfuron [30,45], although a review of imazapic efficacy studies (n = 24) in Montana showed effective but variable results, with one year of application [29].…”
Section: Herbicidementioning
confidence: 99%
“…Morris et al [11], however, determined that spring-applied glyphosate alone reduced B. tectorum cover for two years, and combining with imazapic provided even greater control. Imazapic has been widely used [28][29][30][31] because it provides residual soil activity, which is important for controlling annual plants such as B. tectorum, with early post-emergent fall application recommended [29].…”
Section: Introductionmentioning
confidence: 99%